Pengaruh Faktor Ekonomi Dan Sosial Terhadap Jumlah Anak Yang Dilahirkan Hidup Di Kota Denpasar - Indah Putri, Ni Putu Angelica; Murjana Yasa, I Gst Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 1, Januari 2016 (pp. 1 - 215), 2016)
Fertility is a term in the field of demographics to describe the number of childrenmborn alive. Number of children born alive too high or low will be less good for the progress of the construction, in addition to resulting in a population explosion as well as the lack of human resources. Data collected by observation, questionnaires and interviews unstructured. The sampling technique using quota sampling method with a sample of 139 respondents. Data were analyzed with multiple linear regression analysis technique. Simultaneously obtained results first marriage age, working status, past education, ethnicity and family income affect the number of children born alive in the city of Denpasar. Partially age of first marriage and education last significant negative effect on the number of children born alive in Denpasar while working status, ethnicity and family income did not affect the number of children born alive in the city of Denpasar. R2 values ??in this study amounted to 0.538, or 53.8 percent, this means as much as 53.8 per cent of children born alive in Denpasar in this study is influenced by age at first marriage, work status, past education, ethnicity and family income.
Keywords: fertility; economic; social